Remnants of the fall : - Rolnick, William B. (World Scientific, 2003)
This is a book that sings about the beauty of the fundamental laws of nature. Clear, accurate descriptions for general science readers (no equations in sight!) are punctuated with original, scintillating verses. The reader is taken on a journey through the contemporary understanding of the building blocks of nature and their interactions — the current status of that age-old, intriguing quest. The central role of symmetry is explained in a manner suitable for general science readers, and its splendor is celebrated in verse. The book facilitates understanding of the background and significance of today's scientific discoveries in atomic, nuclear and particle physics. Many of the poems appear as interludes that reinforce the discussions as they amuse the reader, making this informative book a delight to read.